Establishment and parameter analysis of the elasto-visco-plastic constitutive model for straw-potato residue mixture - Guo, Wenbin; Jiang, Xinyang; De, Xuehong; Zhai, Shuo; Shi, Tianyu; Yang, Jian; Zhang, Xuhui; Wang, Zhipeng (Frontiers in Materials, 2023)
In an attempt to characterize the non-linear augmentation of stress as a function of strain during the compression molding process of the straw-potato residue mixture, and to analyze the impact of elasto-visco-plastic deformation on energy consumption and product quality, the present study has established an elasto-visco-plastic constitutive model for the straw-potato residue mixture based on stress-strain test data. The model parameters were obtained through curve fitting, including the elastic modulus E, viscous coefficient K, viscous index n, friction stress σf, and plastic coefficient R1/m.The effects of test factors such as moisture content, feeding amount, compression temperature, and compression speed on these model parameters were analyzed to decipher the elasto-visco-plastic deformation process of the mixture. Additionally, specific energy consumption (SEC) and relaxation ratio (Rr) were employed as test indicators and were subjected to correlation analysis with the model parameters, culminating in the establishment of a multivariate regression equation. The results indicate that the correlation between SEC and the model parameters is quite significant under different test conditions, while Rr is significantly correlated with n, σf, and R1/m only under different moisture contents. This suggests that the energy consumption in the molding of the straw-potato residue mixture is primarily due to overcoming the resistance of elasto-visco-plastic deformation and friction, while the quality of the molding is mainly influenced by the moisture content, thereby establishing a connection with the elasto-visco-plastic parameters. The multivariate regression equation ultimately derived can be used to discern the degree of influence of elastic deformation, viscous deformation and plastic deformation on the specific energy consumption during the compression of the straw-potato residue mixture.